Applied superconductivity : handbook on devices and applications - Seidel, P. (Weinheim : Wiley-VCH, 2015)
This wide-ranging presentation of applied superconductivity, from fundamentals and materials right up to the details of many applications, is an essential reference for physicists and engineers in academic research as well as in industry. Readers looking for a comprehensive overview on basic effects related to superconductivity and superconducting materials will expand their knowledge and understanding of both low and high Tc superconductors with respect to their application. Technology, preparation and characterization are covered for bulk, single crystals, thins fi lms as well as electronic devices, wires and tapes. The main benefit of this work lies in its broad coverage of significant applications in magnets, power engineering, electronics, sensors and quantum metrology. The reader will find information on superconducting magnets for diverse applications like particle physics, fusion research, medicine, and biomagnetism as well as materials processing. SQUIDs and their usage in medicine or geophysics arethoroughly covered, as are superconducting radiation and particle detectors, aspects on superconductor digital electronics, leading readers to quantum computing and new devices.
Includes index.
Includes bibliographical references and index.
Print version record.
Keywords: Superconductivity -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING / Mechanical; SCIENCE / Physics / Electricity; SCIENCE / Physics / Electromagnetism; Superconductivity; Electronic books; Handbooks and manuals; Electronic books